Endothelial Scaffolding Protein ENH (Enigma Homolog Protein) Promotes PHLPP2 (Pleckstrin Homology Domain and Leucine-Rich Repeat Protein Phosphatase 2)-Mediated Dephosphorylation of AKT1 and eNOS (Endothelial NO Synthase) Promoting Vascular Remodeling. Issue 7 (July 2020) - Huang, Jiaqi; Cai, Changhong; Zheng, Tianyu; Wu, Xinyan; Wang, Dongfei; Zhang, Kaijie; Xu, Bocheng; Yan, Ruochen; Gong, Hui; Zhang, Jie; Shi, Yueli; Xu, Zhiyong; et al.
Abstract : Objective: A decrease in nitric oxide, leading to vascular smooth muscle cell proliferation, is a common pathological feature of vascular proliferative diseases. Nitric oxide synthesis by eNOS (endothelial nitric oxide synthase) is precisely regulated by protein kinases including AKT1. ENH (enigma homolog protein) is a scaffolding protein for multiple protein kinases, but whether it regulates eNOS activation and vascular remodeling remains unknown. Approach and Results: ENH was upregulated in injured mouse arteries and human atherosclerotic plaques and was associated with coronary artery disease. Neointima formation in carotid arteries, induced by ligation or wire injury, was greatly decreased in endothelium-specific ENH-knockout mice. Vascular ligation reduced AKT and eNOS phosphorylation and nitric oxide production in the endothelium of control but not ENH-knockout mice. ENH was found to interact with AKT1 and its phosphatase PHLPP2 (pleckstrin homology domain and leucine-rich repeat protein phosphatase 2). AKT and eNOS activation were prolonged in VEGF (vascular endothelial growth factor)-induced ENH- or PHLPP2-deficient endothelial cells. Inhibitors of either AKT or eNOS effectively restored ligation-induced neointima formation in ENH-knockout mice. Moreover, endothelium-specific PHLPP2-knockout mice displayed reduced ligation-induced neointima formation. Finally, PHLPP2 was increased in the endothelia of human atherosclerotic plaques and blood cells from patients with coronary artery disease. Conclusions: ENH forms a complex with AKT1 and its phosphatase PHLPP2 to negatively regulate AKT1 activation in the artery endothelium. AKT1 deactivation, a decrease in nitric oxide generation, and subsequent neointima formation induced by vascular injury are mediated by ENH and PHLPP2. ENH and PHLPP2 are thus new proatherosclerotic factors that could be therapeutically targeted. Abstract : Supplemental Digital Content is available in the text.